Intricacies in Steering the Direction of Science - Fuchs, Lukas (NOvation — Critical Studies of Innovation, 2024)
René von Schomberg’s article (von Schomberg, 2024) makes an invigorating case for the co-responsibility of societal actors to give direction to the pursuit of science. In this reply, I wish to endorse his position as a much-needed reconceptualisation in the face of societal challenges and internal scientific developments. At the same time, I urge that there remain theoretical and practical intricacies in attempting to steer science.